Glossitis by Actinobacillus equuli subsp. equuli in an Equine - Shisei Toma, Hugo; Carvalho, Mariana Bueno; Carvalho, Armando de Mattos; Sales da Cruz, Raquel Aparecida; Schein, Fábio Bernardo; Fernandes Martins, Kamila Peruchi; Monteiro Toma, Claudia Dias; Cabral, Luciano da Silva (Acta Scientiae Veterinariae, 2020)
Background:Actinobacillosis in adult horses is rare, and is often associated with infection due to Actinobacillus equuli subsp. equuli, which is a commensal organism inhabiting the oral cavity of healthy animals. It is an opportunistic pathogen, and the infection usually occurs secondary to another primary disease or due to predisposing factors such as pre-existing lesions, mainly in the oral cavity. Infection may be associated with peritonitis, bacterial endocarditis, pneumonia, enteritis, infectious periorchitis, abortion, and septicemia. This paper aims to describe the clinical, microbiological, and pathological aspects of actinobacillosis in the oral cavity of a horse. Case:A case of actinobacillosis has been reported in a 22-year-old gelding Quarter Horse. According to the owner, the animal presented with progressive weight loss during the previous three months, and leakage of food from the oral cavity. Examination of the oral cavity revealed sharp enamel overgrowths, which had been corrected during a previous dental procedure. However, five days after the procedure, the animal developed halitosis. Ceftiofur sodium (4.4 mg/kg intramuscularly, every 24 h) was prescribed; two days after the commencement of antimicrobial therapy, the animal presented with sialorrhea, bilateral submandibular lymphadenomegaly, protrusion of the tongue, edema of the base of the tongue, cheeks, and gums, in addition to black-colored sores and scales in the oral mucosa, particularly affecting the base of the tongue and gums. Samples from ulcerative lesions found at the base of the tongue and gums were collected using sterile swabs, and culture and antibiogram were requested. Microbiological culture led to the growth of small colonies measuring less than 5 mm in diameter, that were non-hemolytic, slightly whitish in color but non-opaque, smooth and bright in appearance. These were identified as gram-negative rods on microscopy, and further characterized as Actinobacillus equuli subsp. equuli based on the phenotypic and biochemical findings. The antibiogram revealed sensitivity of the organisms to cephalothin and doxycycline, intermediate sensitivity to amoxicillin, and resistance to florfenicol, metronidazole, clindamycin, and sulfazotrim. The complete blood count revealed anemia with a reduction in hemoglobin (10.1 g/dL) and hematocrit (27.9%), neutrophilia (10.670 x 10³ /mm³), and lymphopenia (330 x 10³ /mm³). Decrease in serum albumin (2.0 g/dL) and alkaline phosphatase (91 IU/L), and increase in globulin (4.9 g/dL), aspartate aminotransferase (361 4 IU/L), and urea (123.8 mg/dL) were noted on biochemical analyses. Two days after the onset of acute clinical signs, the animal died; necropsy revealed severe, subacute, fibronecrotic glossitis associated with myriads of basophilic bacteria. Discussion:This report describes an infection of the oral cavity by Actinobacillus equuli subsp. equuli following a dental procedure, a finding compatible with the opportunistic nature of these bacteria. The presence of enamel overgrowths resulted in the formation of traumatic lesions on the oral mucosa and tongue that favored colonization of the bacteria. The case of equine glossitis reported in this study had a similar clinical presentation to the classic actinobacillosis in cattle, also known as “wooden tongue”, an infection caused by Actinobacillus lignieresii; common symptoms in cattle include oral edema, sialorrhea, and dysphagia.